ALOHA-Based Simulation of Safe Fire Distances for Community Safety near Industrial Production Facilities - Irsal Budi Darmawan; Dwita Sutjiningsih; Nana Sugiono (Smart Society, 2025)
Fire and explosion incidents at oil refineries in Indonesia pose serious threats to community safety, environmental sustainability, and economic stability. These risks highlight the need for a comprehensive evaluation of safe distance standards between fuel storage facilities and nearby residential areas. This study aims to assess the safe distance of thermal radiation exposure resulting from a tank fire (pool fire) scenario using the ALOHA (Areal Locations of Hazardous Atmospheres) simulation software, as well as to develop risk mitigation recommendations for surrounding communities. A quantitative, non-experimental approach was employed, utilizing secondary data from PT X and relevant literature. Simulation results indicate that areas within 32 meters of the ISO-6L T-2018 tank are exposed to thermal radiation levels of 6.31 kW/m², a level capable of causing skin burns, with residential settlements located within this zone. Thermal radiation exposure at 6.31 kW/m² may lead to first- to second-degree burns, property damage, long-term health issues, and psychological impacts on residents. Preventive measures and emergency response plans must therefore be developed and implemented to minimize risks and impacts, including community relocation, installation of thermal barriers, safety education, regular radiation monitoring, adoption of control technologies, and enhancement of emergency response infrastructure.